Design of Blessing Ball Throwing Techniques for KRAI 2018 Robot - Diantoro, Rochmat; Aji, Wahyu Sapto (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
Abu Robocon 2018 which was held in Vietnam with the theme "nem con" which means throwing a berkah ball. The Indonesia Abu Robot Contest 2018 made a throwing robot design with different pole height. The parameter that must be achieved is the optimization of the throwing mechanical drive. The thrower mechanics in the KRAI robot can use pneumatically by determining the angle of the robotic thrower. The mechanical tilt angle determines the throwing distance of the berkah ball. To find out the height of this research berkah ball will use python to display the parabolic motion. Based on the results of the study obtained the first test results with a throwing angle of 0 Ëš-115 Ëš get an average value of a distance of 7.37 m, height 273.4 Cm, time 1.42 s and speed of 5.152 m / s. The results of the two test with a throwing angle of 0 Ëš-95Ëš obtained an average distance of 8.78 m, height 352.4 Cm, time 1.63 s and speed 5.381 m / s. It can be concluded that the mechanical tilt angle is leaned forward, the pitching results will be lower. When the angle of inclination is tilted backwards the berkah ball will soar more.